Open Data Readiness Assessments : Lessons Learned - World Bank Group (World Bank, Washington, DC, 2017)
This paper is intended to capture the main lessons learned from conducting Open Data Readiness Assessments and assisting countries with their implementation. Where appropriate examples have been cited, sometimes by name of the country involved where the lesson learned was positive.